PD-1/CTLA-4 Blockade Inhibits Epstein-Barr Virus-Induced Lymphoma Growth in a Cord Blood Humanized-Mouse Model. - Shi-Dong Ma; Xuequn Xu; Richard Jones; Henri-Jacques Delecluse; Nicholas A Zumwalde; Akshat Sharma; Jenny E Gumperz; Shannon C Kenney (PLoS Pathogens)
Epstein-Barr virus (EBV) infection causes B cell lymphomas in humanized mouse models and contributes to a variety of different types of human lymphomas. T cells directed against viral antigens play a critical role in controlling EBV infection, and EBV-positive lymphomas are particularly common in immunocompromised hosts. We previously showed that EBV induces B cell lymphomas with high frequency in a cord blood-humanized mouse model in which EBV-infected human cord blood is injected intraperitoneally into NOD/LtSz-scid/IL2Rγnull (NSG) mice. Since our former studies showed that it is possible for T cells to control the tumors in another NSG mouse model engrafted with both human fetal CD34+ cells and human thymus and liver, here we investigated whether monoclonal antibodies that block the T cell inhibitory receptors, PD-1 and CTLA-4, enhance the ability of cord blood T cells to control the outgrowth of EBV-induced lymphomas in the cord-blood humanized mouse model. We demonstrate that EBV-infected lymphoma cells in this model express both the PD-L1 and PD-L2 inhibitory ligands for the PD-1 receptor, and that T cells express the PD-1 and CTLA-4 receptors. Furthermore, we show that the combination of CTLA-4 and PD-1 blockade strikingly reduces the size of lymphomas induced by a lytic EBV strain (M81) in this model, and that this anti-tumor effect requires T cells. PD-1/CTLA-4 blockade markedly increases EBV-specific T cell responses, and is associated with enhanced tumor infiltration by CD4+ and CD8+ T cells. In addition, PD-1/CTLA-4 blockade decreases the number of both latently, and lytically, EBV-infected B cells. These results indicate that PD-1/CTLA-4 blockade enhances the ability of cord blood T cells to control outgrowth of EBV-induced lymphomas, and suggest that PD-1/CTLA-4 blockade might be useful for treating certain EBV-induced diseases in humans.